Analysis of a terrain characteristic using WAsP and windPRO. (February 2019) - Warudkar, Vilas; Sharma, Pramod Kumar; Ahmed, Siraj
Abstract: This paper investigates the analysis of a terrain characteristics parameter which is responsible for the accurate wind resource estimation for a site. In this paper, the effect of terrain dependent parameters such as Wind shear exponent, Roughness Index, RIX (Ruggedness Index factor) and roughness length has been discussed for a site in Central India Region. Whole one year measured met mast wind data has been taken using anemometer and wind vane at 10 m and 25 m height respectively above ground level. The digitized elevation and roughness model of the corresponding site shows the roughness class 4 (roughness length 1.2525m). The wind data has been extrapolated up to 80m height by using power and log law models which provide the power density near about 120 W/m2. As per the micro sitting guidelines for the virtual wind farm installation 5D X 7D mapping has been selected which Indicates the total power output by installing 8 Vestas V- 90 1.8 MW wind turbine from WAsP is 31.561 GWh and from windPRO is 28.083 GWh.